Sustainable diesel-range liquid fuel production via direct conversion of wet Chlorella sp. KR-1; critical impacts of water. (1st March 2021) - Choi, Il-Ho; Choi, Sun-A; Lee, Jiye; Lee, Hyun-Uk; Hwang, Kyung-Ran
Graphical abstract: Highlights: FAME was produced via the direct conversion of wet algae (various water content). Lipid extraction seemed to the rate-determining step, and water could improve it. Promoted interaction between methanol and algae by water content. FAME production could be catalyzed by FFA derived from the hydrolysis of lipid. 73.9 wt% of FAME yield was accomplished by the adjustable effect of water. Abstract: Biodiesel production through direct conversion of wet algae has various advantages (economic feasibility, land use, emission of greenhouse gas, eco-friendly process, etc.). However, the effect of the water content of wet algae has not yet been clearly determined. The effect of water was thus investigated in the present study via the direct conversion of raw algae using sub- or supercritical methanol for sustainable liquid fuel production. To understand the reactions, gas-, liquid-, and solid-phase products were analyzed by various gas or liquid chromatography tools, a high voltage electron microscope, simulated distillate, etc. As a result, in the direct conversion of raw Chlorella sp. KR-1, lipid extraction appeared to be the rate-determining step and water contained in wet algae could improve the lipid extraction. It was found that 25 wt% water content of algae could increase the yields of fatty acid methyl esters at or below temperature of 250 °C, which could be induced from enhanced interaction between methanol and algal lipids by water. Meanwhile, excessive water content (>25 wt%) would cause undue hydrolysis, leading to lower yields of fatty acid methyl ester. Moreover, thermal decomposition and gasification would progress more in the reaction using wet algae than dried algae at higher temperatures (>250 °C). Consequently, the critical impact of water could be optimized by those parameters toward maximizing the yield of fatty acid methyl esters.